Efektivitas Model Pembelajaran Process Oriented Guided Inquiry Learning (POGIL) terhadap Kemampuan Komunikasi Matematis - Putri Yulia; Maya Riskayani; Selvia Erita (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2021)
This study aims to find out (1) the POGIL learning model effective on mathematical communication skills. (2) conventional learning models are effective against mathematical communication skills. (3) the difference between the POGIL learning model and the conventional model of mathematical communication skills. This research is quasi-experimental research with the research design of The Nonequivalent Posttest Only Control Group Design. The population in this study is all students of grade VII MTS Negeri 02 Kerinci. This study's sample consisted of an experimental class and a control class selected by a random sampling cluster. The research instrument is a test f mathematical communication ability, and the data is analyzed using one-sample t-test statistics and independent t-test samples. This study shows that (1) the POGIL learning model is effective on mathematical communication skills. (2) conventional learning models are ineffective against mathematical communication skills. (3) there is a difference between the POGIL learning model and the conventional model of mathematical communication skills.